INTERNATIONALIZATION: THE UNIVERSITY’S STRATEGY IN AN AGE OF GLOBALIZATION - I. Alyoshina (Вестник университета)
Factors determining the importance of international orientation for the University activity in a globalizing economy, business and resource markets are described. Internationalization is suggested as a key strategy for the University development , providing the country's access to the world markets of education, labor and high-technology sectors of the new economy. A. Osterwalder’s business modeling and I. Ansoff’s growth matrix are recommended for the university internationalization strategy development. The conditions and terms for this strategy implementation are presented.